1993
DOI: 10.1002/bies.950150509
|View full text |Cite
|
Sign up to set email alerts
|

What the papers say: Mammalian cells can trans‐splice. But do they?

Abstract: In trans-splicing, the pre-mRNA products of two different genes are spliced together to form a single, mature mRNA. In one type oE Lrans-splicing, prc-mRNAs of many different genes receive a single, short leader, called spliced leader or SL (diagrammed in Fig. 1 and reviewed in refs. 1-3). This type of trans-splicing was first discovered in the primitive eukaryotes, the trypanosomes, where it is apparcntly the only kind of nuclear mRNA s p l i~i n g '~.~) .Subsequently, it was discovered in nematodes (round tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…This raises the possibility that SL trans ‐splicing could have arisen once, but been transferred laterally throughout diverse phylogenetic lineages. The potential for this is supported by experiments in mammalian cells in which a transfected gene encoding the SL RNA was expressed, assembled with Sm proteins, TMG capped, and then trans ‐spliced onto acceptor 3′ splice sites 94,104. Mammalian cells, representing a lineage that does not normally SL trans ‐splice, were capable of trans ‐splicing once supplied with the gene for the SL RNA.…”
Section: Sl Trans‐splicingmentioning
confidence: 99%
“…This raises the possibility that SL trans ‐splicing could have arisen once, but been transferred laterally throughout diverse phylogenetic lineages. The potential for this is supported by experiments in mammalian cells in which a transfected gene encoding the SL RNA was expressed, assembled with Sm proteins, TMG capped, and then trans ‐spliced onto acceptor 3′ splice sites 94,104. Mammalian cells, representing a lineage that does not normally SL trans ‐splice, were capable of trans ‐splicing once supplied with the gene for the SL RNA.…”
Section: Sl Trans‐splicingmentioning
confidence: 99%
“…However, this proposal was met with a lot of skepticism. In fact, it has been suggested that even if mammalian cells have this capacity, such phenomena are not really occurring (Blumenthal, 1993). Certainly, the SL type of trans -splicing is not apparently taking place in higher eukaryotes.…”
Section: Joining Of Exons From Distinct Pre-mrnas – Evolution Of the mentioning
confidence: 99%
“…28). We cannot exclude the possibility that a single "master" promoter drives mCAT-2 gene expression.…”
Section: Discussionmentioning
confidence: 99%